Psychological problems and related factors among primary healthcare staff in major cities in China during the COVID-19 pandemic - Yi Cui; Ling Li; Xiaofei Mao; Jingzhou Xu; Hao Wang; Shuyu Xu; Tong Su (Scientific Reports)
Abstract This study aimed to explore psychological problems and related factors among frontline primary healthcare workers who belongs to community health service centers and directly provides medical security services to community residents during the COVID-19 in Shanghai. We used a cross-sectional data analysis design to investigate the anxiety and depression levels of 929 frontline healthcare staff (primary healthcare providers, nurses, village doctors, and public health workers) during the Shanghai epidemic.The prevalence of depression among frontline primary healthcare workers was 39.7% (369 cases) and that of anxiety was 30%(279 cases). There was a significant correlation between the depression symptoms and anxiety symptoms. And factors associated with depression were being female, advanced education, expecting psychological interventions, expecting vacations as a reward, and expecting financial rewards. Factors strongly associated with anxiety were being female, expecting psychological interventions, and expecting vacations as a reward. Psychological problems among frontline primary healthcare workers merit more attention during the COVID-19 outbreak, especially those who are vulnerable (e.g., females and those with an advanced education).